2017
DOI: 10.1016/j.jcrs.2017.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of transforming growth factor β–induced gene corneal dystrophies in Chinese refractive surgery candidates

Abstract: The prevalence of the TGF β-induced gene corneal dystrophies in Chinese refractive surgery candidates was estimated to be approximately 0.24%. Genetic testing is recommended to identify and exclude from candidacy all individuals with a TGF β-induced gene dystrophy before elective keratorefractive surgery to avoid causing accelerated postoperative dystrophic deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The reported prevalence of TGFBI corneal dystrophies in Asia is one in 870 in Korea [13] and one in 416 in China [14]. Asia has a high myopia rate, and a study conducted by Holden et al predicted that by 2050, the Asian-Pacific population will have the highest myopia prevalence rate among all populations at 66.4% compared to the global prevalence of 49.8% [12].…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of TGFBI corneal dystrophies in Asia is one in 870 in Korea [13] and one in 416 in China [14]. Asia has a high myopia rate, and a study conducted by Holden et al predicted that by 2050, the Asian-Pacific population will have the highest myopia prevalence rate among all populations at 66.4% compared to the global prevalence of 49.8% [12].…”
Section: Discussionmentioning
confidence: 99%
“…• GCD2 in the South Korean population: 1 in 870 (Lee et al, 2010) • Five most common TGFBI-linked corneal dystrophies in the Chinese population: 1 in 476 (Song et al, 2017) • Overall corneal dystrophies in the US population according to insurance claims data: 1 in 1115 (Musch et al, 2011)…”
Section: Epidemiologymentioning
confidence: 99%
“…Slit-lamp examinations of four cases with corneal opacity in both eyes and one case without corneal opacity were detected with heterozygous p.R124H mutation of TGFBI. The prevalence rate was 0.24% (5/2068 = 24.2/10,000; Song Y. et al, 2017). Analysis of commercial test data used for pre-refractive surgery screening from 600,000 samples from around the world, most of which are from Korea and Japan, demonstrated that the detection rate of TGFBI CDs in Korea is approximately 15/10,000, which is similar to the previously reported detection rate in the Korean population, which is about 11.5/10,000, and higher than the detection rate in the Japanese population 3/10,000 (Lee et al, 2010;Chao-Shern et al, 2019).…”
Section: Discussionmentioning
confidence: 96%